KOMPETENSI PELAUT DALAM PENERAPAN INTERNATIONAL SAFETY MANAJEMEN CODE (ISM- CODE) - Andi Dachlan Sadly (STIE Mandala Jember, 2015)
Kelaiklautan is absolutely filled to the ship to sail, along with the development of the maritime world and the complexity of the problem, then IMO produces guidelanes on Management for Save Operation of ship and for pollution, effective implementation. or better known as the